Medicaid Adult Dental Benefit Impact on Dental Utilization: A University Clinic Setting - Doan, Lynn; Tiwari, Tamanna; Brunson, Diane; Carey, Clifton M. (Frontiers in Public Health, 2017)
Introduction: In 2014 the state of Colorado initiated new dental coverage benefits for adults in the Colorado Medicaid program. The goal of this study was to investigate the utilization and impact of this new dental coverage at the University of Colorado School of Dental Medicine. The utilization of dental services delivered and the numbers of patients in this program were compared before and after the implementation of the benefit. Material and Methods: This retrospective study compared the utilization of services provided 2-years prior and 2-years after the Medicaid adult benefit was made available. Through the University of Colorado School of Dental Medicine (CU- SODM) electronic dental record, all adult Medicaid dental patients’ (ages 21+) charts were extracted for zip code, CDT dental procedure codes, with a focus on tooth extraction compared to tooth saving procedures. Graphical analysis and Pearson’s Chi-Squared tests were applied to assess the statistical significance of procedure utilization changes over time. Results: After implementation of the Medicaid adult benefit, the number of patients seen at the school under this program increased by a factor of 4.5. The geographic range (zip code) increased with a some patients coming from further distances to receive dental care. The number of patients from local zip codes increased by as much as 235 %. There was a 51 % increase in tooth saving procedures, which was statistically significant (P = 0.0013). Additionally, there was a 22 % decrease in extractions, while not statistically significant (P = 0.0992), a downward trend was clear. Discussion: The focus was on the utilization of Medicaid adult benefits at the dental school which was only a small proportion of the state-wide Medicaid population. Therefore, this data is not generalizable for statewide assessments of the program. However, based on the findings at the school clinics, more adult patients utilized the benefits; and chose to receive more tooth saving procedures and less extractions after implementation of the Medicaid adult benefit. This Medicaid study conducted at the CU-SODM 2-years after the adult dental coverage can be used as a baseline for future studies. Word count: 343